An empirical evaluation of ICT tools designed to support water environmental awareness - Swinford, Amanda (Cranfield University, 2005)
The United Nations launched their 'Decade for Sustainable Development', which directly relates to Education for Sustainable Development, a new environmental management system for schools. The formal education process provides a key testing ground for the development of new Infori-nation and Communication Technology (ICT) tools designed to raise environmental awareness. Several types of purpose designed ICT tool are available, but there is a distinct lack of empirical research into their design and effectiveness. Strategic objectives performance takes the central role in the work reported here. A number of strategic objectives of the use of ICT tools were identified; learning, education, trust, motivation, commitment, inclusion, justice and openness. A number of prc-existing software platforms, each specifically designed to provide environmental education and to raise awareness specifically focussing on issues surrounding water were selected and forinally evaluated under controlled conditions with small groups of evaluators. The respondents involved in this investigation included the developers of the tools thernselves, school and postgraduate students (representing users) and experts from academia and industry. The developers of the tools were asked which strategic objectives they considered when they designed their respective tools and the degree to which their tools promoted the strategic objectives was tested in evaluation sessions involving the users. The results from the evaluation sessions involving the users and the experts revealed that strategic objectives such as learning, education, trust and openness were promoted by the tools to some degree, whilst objectives such as justice, motivation and inclusion were promoted to a lesser degree. Whilst it is possible that the tools evaluated simply do not promote the objectives listed, the evaluation methodology adopted in this investigation may go some way to explaining why only certain strategic objectives were found to be promoted. A discussion into the possible methods by which the presence of these strategic objectives could be determined is presented in the concluding chapters of the thesis.
Keywords: Environmental awareness; ICT tools; Design; Evaluation